Mapping Research Trends in Financial Technology (FinTech) and Entrepreneurship Using a Bibliometric Analysis from 2015 to 2024 - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
Financial Technology (FinTech) has rapidly transformed the global financial landscape and created new opportunities for entrepreneurial innovation. Along with the expansion of digital financial services, scholarly attention toward the intersection of FinTech and entrepreneurship has grown significantly over the past decade. This study aims to map the development, collaboration patterns, and thematic evolution of research on FinTech and entrepreneurship using a bibliometric analysis approach. The analysis is based on publications indexed in the Scopus database during the period 2015–2024. Bibliometric mapping and visualization techniques were conducted using VOSviewer to examine co-authorship networks, institutional and country collaborations, keyword co-occurrence, overlay visualization, and density mapping. The results indicate that research in this field has increased substantially, reflecting the growing importance of digital financial innovation in supporting entrepreneurial activities and economic development. The collaboration analysis shows that the United States, China, and several European countries play central roles in global research networks, while emerging economies are increasingly contributing to the literature. Keyword analysis reveals that entrepreneurship, innovation, and fintech are the most dominant themes, with emerging topics such as digital transformation, artificial intelligence, blockchain, financial inclusion, and sustainability gaining increasing scholarly attention. These findings suggest that the FinTech–entrepreneurship research field is evolving into a multidisciplinary domain that integrates technological innovation with financial systems and entrepreneurial ecosystems. This study contributes to the literature by providing a comprehensive overview of the intellectual structure and development trajectory of FinTech and entrepreneurship research and offers insights for future studies focusing on digital financial innovation, sustainable entrepreneurship, and inclusive financial systems.